A Copper Iodide Cluster‐Based Metal–Organic Polyhedra for Photocatalytic Click Chemistry. Issue 5 (8th December 2021) - Wu, Yao; Xie, Mo; Jin, Ji-Kang; Zhang, Zhi-Yin; Hu, Han; Tian, You-Ping; Xiao, Yu-Qing; Ning, Guo-Hong; Li, Dan; Jiang, Xuanfeng
Abstract : Self‐assembly from versatile inorganic secondary building units (SBUs) is an important strategy for constructing metal–organic compounds with sophisticated structures and desired functionality. Herein, a copper(I) iodide cluster‐based metal–organic polyhedra (MOP) (Cu3 I3 )4 L 1 4 (1 ) (L 1 = 1, 3, 5‐trispyridylsulfanylethyl)‐2, 4, 6‐triethylbenzene, 2‐mercaptopyridine) is synthesized. Due to the abnormal geometry of [Cu3 I3 ] SBUs, MOP 1 exhibits a half‐truncated cube topology, which is rarely observed up to date. Compared with commonly used metal ion or clusters, the coordination bond between the [Cu3 I3 ] SBU and the ligand are rather labile in solution evidenced by the theoretical calculations and experimental results. Interestingly, the liable [Cu3 I3 ] SBU endows MOP 1 to photocatalyze the azide–alkyne cycloaddition reaction in aqueous solution with high efficiency, excellent tolerance (>80% isolated yield for 18 examples), and good recyclability. The mechanistic studies reveal a photoinduced electron transfer from the MOP to azide, which is unusual in copper‐catalyzed click reactions. Abstract : A novel copper–iodide cluster‐based metal–organic polyhedra (MOP) with half‐truncated cube topology was self‐assembled through conformation‐adaptive self‐assembly strategy. This MOP containing unprecedent Cu3 I3 cluster node exhibits highly photo‐catalytic activity toward azide–alkyne cycloaddition reaction under the white light‐emitting diode irradiation in water.